Implementation of Talking Stick Learning Model to Improve English Learning Outcomes in Islamic Elementary School - Makrifah, Nurul; Fauzi, Nur (Program Studi Pendidikan Agama Islam (PAI), 2024)
In English subjects, students tend to be embarrassed because they feel inadequate. With a talking stick, students must actively do something that the teacher asks them to do when they get a stick. The objective study of this research is how the implementation of talking stick in English subject, and how the learning outcomes of English can increase. The subject of this research is student of MI An-Nuriyah, class 4. Through Classroom Action Research methods, by qualitative analyze method, and collecting data by interview, observation, and documentation conducted at MI An-Nuriyah Bangkalan, there were significant results, including In cycle I, the percentage of learning outcomes obtained by students was 58.33% and experienced a significant increase in cycle II, classically the percentage of student learning outcomes reached 83.33%, this shows that the application of the Talking Stick Learning Model was successfully tested in subjects English. In cycle II, student learning outcomes exceeded the expected success target, namely ?80%.